2014
DOI: 10.1186/1471-2458-14-821
|View full text |Cite
|
Sign up to set email alerts
|

Long-term stability of return to work after a workplace-oriented intervention for patients on sick leave for burnout

Abstract: BackgroundThe period from the mid-1990s to the mid-2000s saw a rapid increase in long-term sick leave in Sweden, primarily due to mental illness and often related to job burnout. This led to an urge for effective treatment programs that could prevent the often long sick leaves. In 2010 we presented a newly developed work-place intervention method, showing that 89% of the intervention group had returned to work at a 1.5 year follow-up, compared to 73% of the control group. The main aim of this study was to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 15 publications
(34 reference statements)
0
27
0
Order By: Relevance
“…The results showed a more favorable RTW in the intervention group compared to care as usual (Karlson et al, 2010). These results were stable 30 months after conclusion, but only in the younger half of the study sample (Karlson, Jonsson, & Osterberg, 2014).…”
Section: Workplace Interventionsmentioning
confidence: 76%
“…The results showed a more favorable RTW in the intervention group compared to care as usual (Karlson et al, 2010). These results were stable 30 months after conclusion, but only in the younger half of the study sample (Karlson, Jonsson, & Osterberg, 2014).…”
Section: Workplace Interventionsmentioning
confidence: 76%
“…One study of individuals participating in a workplace intervention aimed at increasing RTW after taking sick-leave as a result of burnout showed that the intervention was only effective for younger workers (under 45.5 years of age) [45]. Another intervention aimed at improving RTW following low back pain was only effective for older workers [46].…”
Section: Resultsmentioning
confidence: 99%
“…At follow-up after 1.5 years RTW was increased in the intervention group compared with controls (78). However, in a follow-up after 2.5 years the difference in RTW remained only in subjects younger than 46 years (79). In an RCT by Willert et al (80) patients with stress-related disease (n = 102) were randomized to a stress management intervention or waitlist.…”
Section: Workplace Interventionsmentioning
confidence: 99%